About the so-called «Bug series» of the Middle Bug region (Ukrainian shield). Article 1. The evolution of views and the composition of the «Bug series» - В.П. Кирилюк (Геофизический журнал, 2022)
The name «Bug Series» was introduced into the Precambrian stratigraphic scheme of the Ukrainian Shield more than half a century ago. During this period, ideas about the composition and age of the series changed several times but, until recently, the opinion of various studies about its stratigenic nature remained unchanged. In recent years, many publications have appeared: they express other views on the origin of the «Bug series». Initially, they concerned only individual petrographic groups, such as carbonate and magnetite-bearing rocks, which were attributed to endogenous (magmatic) origin. Later, an opinion about the nonstratigenic origin of the entire «Bug Series» appeared, and some authors proposed to give up on the division of the Early Precambrian granulite complexes into suites. These ideas are only based on the study materials of local objects obtained by drilling and geophysical methods. The author’s conclusions do not take into account the results of regional geological and stratigraphic studies. Simultaneously, with new ideas about the genesis of the «Bug series», an attempt is being made to link its origin with faults and to revise its age.